1997
DOI: 10.1146/annurev.biochem.66.1.385
|View full text |Cite
|
Sign up to set email alerts
|

MODELS OF AMYLOID SEEDING IN ALZHEIMER'S DISEASE AND SCRAPIE: Mechanistic Truths and Physiological Consequences of the Time-Dependent Solubility of Amyloid Proteins

Abstract: Ordered protein aggregation in the brain is a hallmark of Alzheimer's disease and scrapie. The disease-specific amyloid fibrils comprise primarily a single protein, amyloid beta, in Alzheimer's disease, and the prion protein in scrapie. These proteins can be induced to form aggregates in vitro that are indistinguishable from brain-derived fibrils. Consequently, much effort has been invested in the development of in vitro model systems to study the details of the aggregation processes and the effects of endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

85
1,367
3
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,541 publications
(1,466 citation statements)
references
References 94 publications
85
1,367
3
11
Order By: Relevance
“…Protein aggregation is a common hallmark of neurodegenerative disease (Harper & Lansbury, 1997; Trojanowski et al , 1998; Koo et al , 1999; Aguzzi & O'Connor, 2010) although the mechanisms of toxicity remain poorly understood. Different neurodegenerative diseases, or their subtypes, are often distinguished by the specific patterns of protein aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Protein aggregation is a common hallmark of neurodegenerative disease (Harper & Lansbury, 1997; Trojanowski et al , 1998; Koo et al , 1999; Aguzzi & O'Connor, 2010) although the mechanisms of toxicity remain poorly understood. Different neurodegenerative diseases, or their subtypes, are often distinguished by the specific patterns of protein aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…The misfolding of a unique peptide or protein into b-sheet-rich fibrous structures is proposed to be a key step in the onset and development of these diseases [3,5]. The amyloid deposits cause cell dysfunction, death, and subsequently severe impairment in tissues of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies concentrated on the central sequence of Ab peptide, suggesting that Ab [14][15][16][17][18][19][20][21][22][23] [12] and Ab [16][17][18][19][20][21][22] [13] are the fibril-generating peptide fragments, other study indicated that the Ab 36-42 fragment could form very stable fibril with highly ordered structure and is a key factor determining the aggregation of Ab 1-42 [14]. This renders us to reconsider why only Ab 40 and Ab 42 peptides are neurotoxic and why Ab 42 aggregates into fibrils faster than Ab 40 [5]. a-Syn is another amyloidogenic protein of great interest that is closely associated with the Lewy bodies in Parkinson disease [15,16].…”
Section: Introductionmentioning
confidence: 99%